Cortical pattern of complex but not simple movements is affected in writer's cramp: a parametric event-related fMRI study - Havránková, Petra; Walker, Nolan D; Operto, Grégory; Sieger, Tomáš; Vymazal, Josef; Jech, Robert (Clinical neurophysiology, 2012)
OBJECTIVE: Patients with writer's cramp (WC) were studied for differences in cortical activation during movements likely to induce WC (complex movements) and movements which rarely lead to dystonia (simple movements). METHODS: Eleven WC patients (10F, 1M, mean age 41.5 ± (SD)7.2 years) and eleven age matched controls were examined for Blood oxygenation-level dependent (BOLD) 1.5 T fMRI. The complex task consisted of writing a single letter or random drawing using an especially adapted joystick with the line of trajectory visualized or hidden. The simple task consisted of self-initiated fingers flexion/extension using the affected hand. RESULTS: Unlike the controls, WC patients performing complex movements exhibited a lower BOLD signal in the primary sensorimotor cortex and in the posterior parietal cortex bilaterally. A hypoactivation was also observed in the right secondary somatosensory area, in the right anterior insula and in the left premotor cortex (p < 0.05 corrected). No significant inter-group differences were found for simple movements. CONCLUSIONS: Although WC patients' complex movements during fMRI were never associated with dystonic cramp, they exhibited an abnormally low cortical activity. This phenomenon was not observed in simple movements and was unrelated to the character of handwriting or to visual feedback. SIGNIFICANCE: Our results support the dualistic behavior in the sensorimotor system in WC.
Keywords: světelná stimulace; Humans; magnetická rezonanční tomografie; Image Processing, Computer-Assisted; temenní lalok; algoritmy; lidé; Botulinum Toxins; antidyskinetické látky; počítačové zpracování obrazu; Somatosensory Cortex; mozková kůra; Movement; dystonické poruchy; somatosenzorické korové centrum; Psychomotor Performance; Female; psychomotorický výkon; lidé středního věku; Anti-Dyskinesia Agents; Dystonic Disorders; Handwriting; psaní rukou; Male; Oxygen; Parietal Lobe; feedback psychologický; kyslík; botulotoxiny; Adult; Motor Cortex; Algorithms; dospělí; Biomechanical Phenomena; Cerebral Cortex; motorické korové centrum; Photic Stimulation; Feedback, Psychological; Middle Aged; biomechanika; ženské pohlaví; mužské pohlaví; Magnetic Resonance Imaging; pohyb